ChemInform Abstract: A Convenient and Efficient C—OH Bond Activation, PdCl2(PPh3)2 Catalyzed, C—C Bond Formation of Tautomerizable Quinolinones with the Aid of BOP Reagent and Boronic Acids. Issue 12 (March 2015) - Kumar, Yadavalli Suneel; Dasaradhan, C.; Prabakaran, Kamalakannan; Khan, Fazlur‐Rahman Nawaz; Jeong, Euh Duck; Chung, Eun Hyuk; Kim, Hyun Gyu
Abstract 23 examples